COLLABORATION IN TEACHING: THE ROLE OF TEACHERS, STUDENTS, AND TECHNOLOGY IN EFFECTIVE LEARNING - Darwin, David (PT. Hafasy Dwi Nawasena, 2025)
This study aims to analyze the roles of teachers, students, and technology in building effective collaborative learning. Using descriptive qualitative research methods, data were collected through in-depth interviews, observations, and documentation with teachers and students in a school environment that has implemented collaboration-based learning. The results show that teachers act as facilitators, motivators, and directors, students play an active role in discussions and collaboration, while technology functions as an interactive medium that expands the learning space. Factors supporting collaboration include teacher pedagogical competence, student motivation, an open learning culture, and technological infrastructure support. The main obstacles are limited access to technology, low digital literacy, and differences in student engagement levels. Overall, the collaboration of these three elements has been proven to increase engagement, motivation, and learning effectiveness, while also emphasizing the need for an adaptive collaboration model in the digital era.